The Russia-Ukraine war's impact on global food markets: A historical perspective - Glauber, Joseph W.; Laborde Debucquet, David; Swinnen, Johan (International Food Policy Research Institute, 2023)
The Russia-Ukraine war has focused global attention on the key economic roles those countries play as major exporters of agricultural commodities. Over the 2019–2021 period, they accounted for 12% of global agricultural trade on a kilocalorie basis, with a combined market share of 34% for wheat, 26% for barley, 17% for maize, and 75% for sunflower oil. The war has scrambled this picture, with Ukraine’s exports falling dramatically, and Russia’s falling, then recovering. While the Black Sea region has historically been a major grain producer, its emergence as a major world exporting region is a relatively recent phenomenon. From the 1970s until the early 2000s — the decades imme diately before and after the collapse of the Soviet Union — Russia and Ukraine were net grain importers. This post examines how and why Russia and Ukraine became such important factors in 21st century global food markets — and thus why the war poses a continuing threat to global food security